Loss Aversion of Time: Serving School Lunches Faster without Impacting Meal Experience. Issue 6 (2nd November 2018) - Sharma, Amit; Moon, Joonho; Bailey-Davis, Lisa
ABSTRACT: Loss aversion has been extensively studied in economics, but there is less discussion of it in the context of time. Results from a field experiment conducted in a U.S. public school lunch cafeteria suggest that students could be loss averse to time and that interventions, such as a pre-plated service lane could increase the speed of service and guide students to make better food choices. Faster, pre-plated service lanes may leverage loss aversion bias, be beneficial for larger schools, reduce wait time for students, and thereby increase their satisfaction with the service process.